A Monte Carlo Simulation study on the design and optimization of collimators for non-collinear cascade gamma-ray correlation emissions in medical imaging - Leonid Leopold Nkuba; Innocent Lugendo (Brazilian Journal of Radiation Sciences)
This study focused on designing and optimizing collimators for cascade gamma-ray imaging through Monte Carlo simulations. The trapezoidal-shaped collimator blocks, designed in the Geant4 application for emission tomography (GATE) environment, were attached to a simulated small animal GATE - PET model. The collimators were optimized by simulating septa thicknesses from 0.2 mm to 1.2 mm, in 0.2 mm increments. A 1.0 MBq 111In source having radius of 0.25 mm was used as the cascade gamma-ray emitter. Sixteen trapezoidal tungsten collimator blocks were designed, each with a 16.31 mm × 37.5 mm surface facing the detector crystals, and a 12.33 mm × 37.5 mm surface facing the scanned object. Each block featured 105 parallel rectangular holes arranged in a 7 × 15 array, with a length of 10.0 mm, resulting in a ring-like collimator with a 41.0 mm outer radius. The designed collimator, intended for small animal imaging, prioritizes resolution. Hence, a collimator with 1.0 mm septa and hole sizes of 1.5 mm × 0.7 mm, offering spatial resolutions of 7.6 mm and 4.1 mm in the axial and transaxial directions, respectively, was chosen. The collimators demonstrated energy resolution of approximately 8.96% and 10.10% at 171.3 keV and 245.4 keV, respectively, within a 10% energy resolution threshold set during simulations. Besides, the reconstructed source positions ranged from 81.1% to 100% of the true simulated source positions within the field of view. The optimized collimator design presents a viable solution for imaging small animals’ internal organs, with sizes exceeding 7.6 mm.